2019
DOI: 10.1111/php.13078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Titanium Dioxide Film Thickness on Photocatalytic and Bactericidal Activities Against Listeria monocytogenes

Abstract: Structural, microstructural and bactericidal surface properties of TiO 2 -coated glass substrates elaborated by reactive Radiofrequency sputtering are investigated. As pathogenic bacteria in biofilms are a major concern in food industries due to their growing resistance to cleaning and sanitizing procedures, the development of photoactive surfaces exhibiting bactericidal properties is acknowledged as an effective approach to tackle bacterial contaminations. Our principal aim concerns the study of the photoacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…11 Applying TiO2-incorporated surfaces for self-disinfection enabled bacterial inactivation, even up to complete mineralization [12][13] on a wide range of Gram-negative and Gram-positive bacteria species. Aside from irradiation source power, 14 treatment time 15 and matrix (or substrate)-related factors, [16][17] the intrinsic physico-chemical properties of TiO2 greatly affect the photocatalytic oxidation performance of the coating by influencing the amount, recombination rate and diffusion length of the photogenerated charges. 18 The role of TiO2 itself was addressed in many studies by comparing the bactericidal performance of new TiO2 coatings 19 to that made of P25 TiO2, 20 the commercial photocatalyst largely admitted as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…11 Applying TiO2-incorporated surfaces for self-disinfection enabled bacterial inactivation, even up to complete mineralization [12][13] on a wide range of Gram-negative and Gram-positive bacteria species. Aside from irradiation source power, 14 treatment time 15 and matrix (or substrate)-related factors, [16][17] the intrinsic physico-chemical properties of TiO2 greatly affect the photocatalytic oxidation performance of the coating by influencing the amount, recombination rate and diffusion length of the photogenerated charges. 18 The role of TiO2 itself was addressed in many studies by comparing the bactericidal performance of new TiO2 coatings 19 to that made of P25 TiO2, 20 the commercial photocatalyst largely admitted as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…The annealing temperature for the anatase phase to change into the rutile phase is about 600 to 800 • C [27]. Furthermore, TiO 2 is liable to crystallize and transform to rutile with the increase of the thickness [28,29]. However, it is worth noting that ZT5 has similar thickness with ZT2, ZT3, and ZT4.…”
Section: Resultsmentioning
confidence: 99%
“…Bartomeuf et al examined a photoactive layer, which showed increased efficiency to 400 nm threshold against L. monocytogenes . In addition, the number of bacteria decreased significantly after 20 min UV-A lighting [ 68 ].…”
Section: Discussionmentioning
confidence: 99%